Compliance control as a risk minimization tool in anti-money laundering and terrorist financing systems: the experience of Russia and Kazakhstan ("Journal "U". Economy. Management. Finance.", 2024)
The article is devoted to the study of compliance control as a key tool for minimizing risks in the field of countering money laundering and terrorist financing (AML/CFT) in Russia and Kazakhstan. The national peculiarities of the legislative framework, the practice of applying international standards (FATF), as well as approaches to risk management in the banking sector of both countries are considered. The analysis showed that in Russia, the emphasis is on creating a unified legal framework, whereas in Kazakhstan, attention is focused on improving monitoring and risk management procedures. Despite the achievements, the problems related to the identification of questionable transactions and the implementation of the KYC principle ("know your customer") remain unresolved. The results of the study have theoretical significance for the study of compliance control and practical value for improving risk management systems in the financial sector.
Keywords: compliance control; AML/CFT; FATF; risk management; banking system; financial institutions; financial monitoring; «know your customer» principle; artificial intelligence technologies; cultural factors; Russia; Kazakhstan